Temporalités marchandes et rapport à l'avenir dans les interactions bancaires - Xavier Roux (Temporalités)
Observing advisor-customer interactions in banks provides interesting data to analyze what happens when two different approaches to time come together: those promoted by the banks and those belonging to the family sphere, the home and the social worlds in which they are embedded. In this paper, such data allow us to test the hypothesis that the Bourdieu exemplified approach of collective forms of anticipating the future in the context of the deep social changes taking place in Algeria in the 1950’s, can also apply to the less spectacular evolutions in societies with a longer capitalist past, such as banks opening up to market laws and practices as has been the case in France over the last few decades. Market procedures have deeply modified the banks’ commercial strategies. They have contributed to promoting new forms of economic action aimed at customers, bearing a relation to the future, including a belief in progress, the need to have projects and make quick decisions. That way of relating to the future is sometimes interiorized by customers, but it is sometimes specifically rejected by them.